2012
DOI: 10.1186/1471-2377-12-123
|View full text |Cite
|
Sign up to set email alerts
|

Temporal profile of body temperature in acute ischemic stroke: relation to stroke severity and outcome

Abstract: BackgroundPyrexia after stroke (temperature ≥37.5°C) is associated with poor prognosis, but information on timing of body temperature changes and relationship to stroke severity and subtypes varies.MethodsWe recruited patients with acute ischemic stroke, measured stroke severity, stroke subtype and recorded four-hourly tympanic (body) temperature readings from admission to 120 hours after stroke. We sought causes of pyrexia and measured functional outcome at 90 days. We systematically summarised all relevant p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
35
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 30 publications
7
35
0
4
Order By: Relevance
“…Other studies have indicated that it is not admissional body temperature that is associated with adverse outcomes of stroke, but the temperature peak occurring a few days after the stroke (18)(19)(20). The present study revealed that the more serious the stroke and the higher the NIHSS score, the more the body temperature increased.…”
Section: A B Csupporting
confidence: 61%
“…Other studies have indicated that it is not admissional body temperature that is associated with adverse outcomes of stroke, but the temperature peak occurring a few days after the stroke (18)(19)(20). The present study revealed that the more serious the stroke and the higher the NIHSS score, the more the body temperature increased.…”
Section: A B Csupporting
confidence: 61%
“…However, no source of infection could be found in almost half of the hyperthermic patients in a previous study [8]. Fever could also be the result of an inflammatory response of the body to the infarcted tissue.…”
Section: Discussionmentioning
confidence: 92%
“…Several studies have suggested that this is limited to body temperatures on admission or during the first day, [3, 5, 6, 10, 11, 13] whereas others have found that this relation persists for up to one week [2, 79, 12]. These inconsistencies may be attributed to differences in study designs and populations, [8] for example related to the time of admission, [13] the definition of a poor outcome outcome, [11] and selection of patient populations [3, 10]. …”
Section: Introductionmentioning
confidence: 99%
“…BT has been reported to arise 4 to 6 hours after stroke onset through a systemic response to brain insult and this elevation reaches a peak between 1 and 2 days after stroke. 2, 4, 30 Accordingly, BT measured in the subacute period, 4-48 hours after onset are likely to be directly related to stroke severity, while BTs measured in the acute period, within the first 4 hours, appear to be inversely related to stroke severity.…”
Section: Discussionmentioning
confidence: 97%
“…1-4 However, in the hyperacute stage, during the first 1-6 hours after onset, studies have not uniformly supported an association of presenting hyperthermia with increased severity. 1-10 Indeed, a few studies have suggested a reverse relationship: increased initial BT associated with less severe neurologic deficits and more neurologic improvement within 24 hours.…”
Section: Introductionmentioning
confidence: 99%